Philosophy of Technology and Engineering Sciences. - Gabbay; Meijers, Anthonie; Thagard, Paul (Elsevier Science & Technology, 2009)
The Handbook Philosophy of Technology and Engineering Sciences addresses numerous issues in the emerging field of the philosophy of those sciences that are involved in the technological process of designing, developing and making of new technical artifact.